Cellulose nanocrystals isolated from oil palm trunk - Junidah, Lamaming; Rokiah, Hashim; Othman, Sulaiman; Leh, Cheu Peng; Tomoko, Sugimoto; Noor Afeefah, Nordin (Elsevier B.V., 2015)
In this study cellulose nanocrystals were isolated from oil palm trunk (Elaeis guineensis) using acid hydrolysis method. The morphology and size of the nanocrystals were characterized using scanning electron microscopy and transmission electron microscopy. The results showed that the nanocrystals isolated from raw oil palm trunk (OPT) fibers and hot water treated OPT fibers had an average diameter of 7.67 nm and 7.97 nm and length of 397.03 nm and 361.70 nm, respectively. Fourier Transform Infrared spectroscopy indicated that lignin and hemicellulose contents decreased. It seems that lignin was completely removed from the samples during chemicaltreatment. Thermogravimetric analysis demonstrated that cellulose nanocrystals after acid hydrolysis had higher thermal stability compared to the raw and hot water treated OPT fibers. The X-ray diffraction analysis increased crystallinity of the samples due to chemical treatment. The crystalline nature of the isolated nanocrystals from raw and hot water treated OPT ranged from 68 to 70%.